Awareness of salt restriction is not reflected in the actual salt intake in Japanese hypertensive patients. (August 2015) - Takahashi, Nobuyuki; Tanabe, Kazuaki; Adachi, Tomoko; Nakashima, Ryuma; Sugamori, Takashi; Endo, Akihiro; Ito, Takafumi; Yoshitomi, Hiroyuki; Ishibashi, Yutaka
Abstract Objectives: The Japanese guidelines for hypertension management recommend reducing salt intake to <6 g/day for hypertensive patients. However, it is not currently known whether hypertensive patients' awareness of the recommended reduced salt diet correlates with their actual intake. Therefore, the purpose of this study was to investigate the relationship between actual salt intake of Japanese hypertensive patients and their awareness of the recommended guidelines for reduced dietary salt intake. Methods: In total, 236 outpatients (146 males and 90 females) with a mean age 69.7 ± 12.5 years were included in this study. Daily dietary salt intake was estimated using sodium and creatinine concentrations detected in spot urine samples. The patients filled out a questionnaire regarding their awareness of recommended salt restriction for hypertension management. The questionnaire distinguished the patients' awareness of recommended salt restriction in four levels (low, moderate, high and very high). Results: The mean estimated salt intake was 9.72 ± 2.43 g/day. Patients' awareness regarding salt intake in all levels provided in the questionnaire did not correlate with actual salt intake (p = 0.731). Conclusion: Our results demonstrated that Japanese hypertensive outpatients consumed higher levels of salt than the target value recommended by Japanese guidelines. There was no correlation between actual salt intake and patients' awareness of the recommended reduction in salt. These results suggest that monitoring salt intake and informing patients of their actual salt intake are necessary for effective hypertension management.